2019
DOI: 10.1002/jper.19-0132
|View full text |Cite
|
Sign up to set email alerts
|

A point‐of‐care test of active matrix metalloproteinase‐8 predicts triggering receptor expressed on myeloid cells‐1 (TREM‐1) levels in saliva

Abstract: Background This cross‐sectional study aims to investigate if a point‐of‐care (PoC) test of active matrix metalloproteinase‐8 (aMMP‐8) predicts levels of inflammation amplifier triggering receptor expressed on myeloid cells‐1 (TREM‐1) and its putative ligand the neutrophil peptidoglycan recognition protein 1 (PGLYRP1) in saliva. Methods Forty‐seven adolescents, aged 15 to 17 years, were tested with aMMP‐8 PoC test, which was followed by a full‐mouth clinical examination of the assessment of periodontal, mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…1 illustrates the ability of aMMP-8 PoC mouthrinse test compared to aMMP-8 IFMA measured from saliva, and it clearly shows how saliva is inferior to mouthrinse in aMMP-8 measurements related to identifying periodontal health and disease. There is a significant association between the aMMP-8 PoC mouthrinse test result and aMMP-8 IFMA levels in saliva in this sample of adolescents, as has been shown recently by Räisänen et al (2019b). However, if patient's periodontal health is considered, the distinction of salivary aMMP-8 IFMA measurements is far from perfect between a positive and negative test result.…”
supporting
confidence: 68%
“…1 illustrates the ability of aMMP-8 PoC mouthrinse test compared to aMMP-8 IFMA measured from saliva, and it clearly shows how saliva is inferior to mouthrinse in aMMP-8 measurements related to identifying periodontal health and disease. There is a significant association between the aMMP-8 PoC mouthrinse test result and aMMP-8 IFMA levels in saliva in this sample of adolescents, as has been shown recently by Räisänen et al (2019b). However, if patient's periodontal health is considered, the distinction of salivary aMMP-8 IFMA measurements is far from perfect between a positive and negative test result.…”
supporting
confidence: 68%
“…Our findings indicate that the aMMP-8 mouthrinse PoC/chairside test [10,12,[14][15][16][17][18][19][20][21][22][23][24][25][26] can be implemented as the staging and grading biomarker in the new classification system of periodontitis [1]. In this regard, a previous study by Räisänen et al [21] showed that mouthrinse aMMP-8 measurements are better and more precise in identifying periodontal health and disease among adolescents in comparison to saliva aMMP-8 measurements.…”
Section: Main Textmentioning
confidence: 63%
“…A.G. performed a full-mouth clinical examination for each patient to assess their periodontal and oral health, after which each patient's aMMP-8 mouthrinse test result was read. Firstly, aMMP-8 levels in mouthrinse were significantly lower among healthy patients compared with patients in more severe periodontitis stages and grades (Kruskal-Wallis test, p < 0.01; Figure 1), as would be expected from an effective diagnostic tool to classify periodontal health and disease [14][15][16][17][18][19][20][21][22][23][24][25][26]. This result is also in agreement with previous studies that have shown that aMMP-8 predicts very well future periodontal breakdown (positive predictive values range between 81.8%-94.7%) [35].…”
Section: Main Textmentioning
confidence: 89%
See 2 more Smart Citations